Aplikasi Suhu terhadap Mortalitas Hama Sitophilus zeamais dan Tribolium castaneum pada Jagung - Susanti, Rini; Risnawati, Risnawati; Fadillah, Wizni; Lisdayani, Lisdayani; Puspita, Riana (Agrotechnology Research Journal, 2022)
Warehouse pests are nuisance pests that cause a decrease in the quality and quantity of harvested grains. Sitophilus zeamais and Tribolium castaneum are important warehouse pest of corn. Apart from attacking corn grains, this pests also attacks rice, wheat, sorghum, soybeans, grain/rice, and green beans. Temperature is a very influential aspect in the life of all insect species, including warehouse pests. This study aimed to determine the appropriate temperature range for controlling warehouse pests of Sitophilus zeamais and Tribolium castaneum which does not interfere with health and is also safe for consumers. This research was conducted at the Pest Laboratory, Faculty of Agriculture, UMSU. The method used was factorial completely randomized design (CRD), the first factor was the use of temperature and the second factor was duration of heating with three replications. The results showed that the application of a temperature of 100 0C for 120 seconds or 150 0C for 60 seconds could cause the mortality of S. zeamais and T. castaneum pests to reach 100% in corn grains in storage.